Patterns, trends and correlates of ten major reported crimes in Ondo State, Nigeria (2019)
We analysed the trend, patterns, and correlates of ten major crimes among Local Government Areas (LGAs) in Ondo State. The number of reported crimes from 2007 to 2016 were used to assess the trend in crimes, while the reported number of crimes in 2007 and 2010 from the 18 LGAs were used for the analysis of the spatiotemporal distribution and pattern of crimes. The reported number of murders, rape and indecent assault, assault, pretence/cheating, breach of the public peace, kidnapping and forgery increased while burglary and armed robbery declined. Akure South, Ondo West, Akure North, and Ilaje LGAs had the highest reported crimes. Nearly all the crimes exhibited a random distributional pattern in 2007 and 2010 except assault and kidnapping. There was a significant difference between the number of reported crime in urban and rural LGAs (F( 1,358)=4.148) while the number of hotels and population density was highly correlated with some crimes. Availability of relatively long-time data provides opportunity to understand the spatiotemporal trend, pattern and correlates of major crimes in Ondo State, Nigeria.